Corporate Social Responsibility and Reputation: A Study on Top 100 Companies Operating in India - Loopamudra Baruah; N.M. Panda (Universitas Pasundan, 2022)
The corporate social responsibility (CSR) performance of a company enhances a company’s credibility, thereby influencing the perception of its stakeholders in improving the corporate reputation of a company. This study examines this claim by empirically investigating the CSR performance of India’s top 100 companies and its impact on their reputational status. We have employed the panel-corrected standard error model by controlling companies’ financial performance, size, age, and market risk to analyze the impact of CSR performance on reputation. The result of the analysis is contradictory to the common belief that CSR positively impacts reputation building. Although this study is not novel in nature, it is incremental to the current literature as this study is conducted from an Indian perspective (where no study has been conducted as per our knowledge). This study uses data that are more objective and concrete than those of previous studies, making this study another valuable addition to the extant literature as it is an improvement over the previous study.